2001
DOI: 10.1148/radiology.218.1.r01ja13188
|View full text |Cite
|
Sign up to set email alerts
|

Focal Arterial Injuries of the Proximal Extremities: Helical CT Arteriography as the Initial Method of Diagnosis

Abstract: Helical CT arteriography can be performed as the initial diagnostic method in most patients suspected to have focal arterial injuries of the proximal portions of the extremities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
109
0
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(121 citation statements)
references
References 28 publications
0
109
0
12
Order By: Relevance
“…The various possible sites of pseudoaneurysm rupture include gut, biliary tree, thoracic, peritoneal, pelvic and retroperitoneal spaces [10], which may manifest as sentinel bleed from the drain, hemetemesis, malena, splenic rupture or subcapsular hepatic hematoma [8,11]. The diagnosis of pseudoaneurysms has been revolutionised by varying imaging modalities like duplex Doppler ultrasonography (US), magnetic resonance (MR) angiography and helical computed tomography (CT) angiography [6,12] although the conventional angiography remains the gold standard of reference [13].…”
Section: Discussionmentioning
confidence: 99%
“…The various possible sites of pseudoaneurysm rupture include gut, biliary tree, thoracic, peritoneal, pelvic and retroperitoneal spaces [10], which may manifest as sentinel bleed from the drain, hemetemesis, malena, splenic rupture or subcapsular hepatic hematoma [8,11]. The diagnosis of pseudoaneurysms has been revolutionised by varying imaging modalities like duplex Doppler ultrasonography (US), magnetic resonance (MR) angiography and helical computed tomography (CT) angiography [6,12] although the conventional angiography remains the gold standard of reference [13].…”
Section: Discussionmentioning
confidence: 99%
“…There is little to no evidence in the literature specifically studying the use of CTA angiography in subclavian artery injuries, however, several large series of CT in proximal extremity injury including the subclavian and axillary artery have found excellent sensitivity and specificity. A study of 142 CTA angiograms, including 7 subclavian artery injuries, found a sensitivity of 95.1% and specificity of 98.7% (Soto, et al, 2001). In a study of 41 stable patients with penetrating thoracic trauma CTA angiography did not miss any injuries in 9 patients who underwent both CT and traditional angiography (LeBlang & Dolich.…”
Section: Subclavian Arterymentioning
confidence: 99%
“…Injury can present as focal narrowing, occlusion, thrombosis, pseudoaneurysm, extravasation, arteriovenous fistula, dissection, and intimal flap (Figure 2a, 2b). There is some evidence that arterial spasm may result in false positives on CTA (Figure 3), while conversely small intimal flaps may not be detected and result in false negatives (Rieger, et al, 2006;Soto, et al, 2001). Confirmatory angiography may be useful in cases of suspected spasm, vs. repeat imaging following resuscitation, while in the case of intimal flaps, the need for endovascular or open intervention is rare even in series with long term follow up (Dennis, et al, 1998).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the usefulness of US in the evaluation of deep arteries is limited, with low sensitivity. The Doppler has also been found to be less reliable in arterial injuries of the proximal extremities [13]. Moreover, US is operator-dependent, and the evaluation of vessels in trauma patients with fractures or hematomas may be difficult.…”
Section: Anatomy and Probable Injury Mechanismmentioning
confidence: 99%